SOME PRODUCTIVE TRAITS OF CYPRIOT GOATS AND ITS EFFECT ON GENETIC MANIFESTATIONS OF THE FADS1 GENE (World Bulletin of Public Health, 2023)
This study was conducted with the aim of identifying some genetic features of the FADS1 gene and its relationship to some productive traits of local goats, studying the components of milk from protein, fat, lactose and nonprotein mineral elements, estimating the live weight of mothers, birth weight, weaning weight, length of milk season and gene-duplication, the effect of live weight was significant (P